+0  
 
0
92
1
avatar

I need help with this asap please

Guest May 17, 2018
 #1
avatar+88897 
+1

f(x)  =  x^4  - 9           g (x)  =  x^3 + 9

 

So....  (f * g) x  =   f(x) * g(x)  =

 

[ x^4  - 9 }  *  [ x^3 + 9 ]   =

 

x^7 + 9x^4  - 9x^3  - 81

 

 

 

cool cool cool

CPhill  May 17, 2018

19 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.